2012
DOI: 10.4172/2161-1009.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biochemical Composition of Honey Samples from North-East Nigeria

Abstract: Natural honey is one of the most widely sought products due to its unique properties, which are attributed to the influence of the different groups of substances it contains. Honey is used for nutritional, medicinal and industrial purposes and it is an important commodity in the international market; serving as foreign exchange earner for many countries. In Nigeria, honey production (beekeeping) has the potential to develop as a prime agro-horticultural and forest-based industry which can be a major foreign ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
50
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 19 publications
(27 reference statements)
14
50
3
4
Order By: Relevance
“…However, in some Bangladeshi honey samples the mean ash percentage was 0.36 ± 0.08% (Asaduzzaman et al 2015). Buba and her colleagues studied 18 honey samples from Nigeria and found that the ash percentage was 0.42 ± 0.009%, which is higher than our findings (Buba et al 2013). Our results…”
Section: Resultscontrasting
confidence: 75%
“…However, in some Bangladeshi honey samples the mean ash percentage was 0.36 ± 0.08% (Asaduzzaman et al 2015). Buba and her colleagues studied 18 honey samples from Nigeria and found that the ash percentage was 0.42 ± 0.009%, which is higher than our findings (Buba et al 2013). Our results…”
Section: Resultscontrasting
confidence: 75%
“…This showed the natural feeding of the honey bees and high quality of the honey produced from the farms [20]. The results were further compared with previous published results (sugars in honey) for honey samples in Nigeria [5,18,23,24]. The results showed no significant difference from previous studies.…”
Section: Results and Discussion Physicochemical And Sugar Analysessupporting
confidence: 54%
“…As previously reported, the typical constituents of honey by dry matter is sugar, with small amounts of about 22 additional complex sugars and other constituents like pigments, acids and minerals that bring about unique honey types. Subsequently, honeybees are related to the identity and quality of their honey, however, there are not many studies that establish the stability of chemical compounds present in honey and ensuring that honey consumption are devoid of toxic compounds for human health [3,4]. A study conducted on stability of Nigerian honey showed that if natural harvested honeys are produced hygienically and stored, that its stability can be up to 2 years [5], while the geographical and botanical origin of the flora, type and activity of the bee can also affect the quality and honey composition [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pH increase from the lowest to the highest dilution was slight and was ranging from 0.23 pH units for chestnut honey, to 0.39 pH units for black locust. Such slight changes in pH upon honey dilution were not surprising, since it is well known that honey acts as a buffer (Buba et al, 2013). (Brudzynski, 2006;Brudzynski et al, 2011;Brudzynski et al, 2017), by measurement of oxygen concentration (decomposition of H 2 O 2 by exogenously added catalase) (Bang et al, 2004), while only Cooke et al (2015) measured hydrogen peroxide content in honeys using MQuant test strips, but examined special types of honey.…”
Section: Resultsmentioning
confidence: 99%